Arabidopsis B-BOX DOMAIN PROTEIN14/15/16 form a feedback loop with ELONGATED HYPOCOTYL 5 and PHYTOCHROME-INTERACTING FACTORs to regulate hypocotyl elongation - Zeeshan Nasim; Nouroz Karim; Hendry Susila; Ji Hoon Ahn (Current Plant Biology)
Light-regulated developmental processes such as photomorphogenesis and flowering play important roles in the plant life cycle, from seedling emergence to reproduction. Three members of the Arabidopsis thaliana B-BOX DOMAIN PROTEIN (BBX) family, BBX14, BBX15, and BBX16 (hereafter BBX14/15/16), redundantly regulate flowering time, but whether this genetic redundancy also affects the regulation of photomorphogenesis remains unclear. Here, we show that light induces BBX14/15/16 expression primarily in the hypocotyl, where BBX14/15/16 redundantly repress hypocotyl elongation. PHYTOCHROME-INTERACTING FACTORs (PIFs) negatively regulate BBX14/15/16 expression mainly through GOLDEN-LIKE proteins (GLKs); however, analyses of ChIP-seq data showed that PIFs are recruited to the BBX14/15/16 loci and can also regulate these genes independently of GLKs. ELONGATED HYPOCOTYL 5 (HY5), a major regulator of photomorphogenesis, also directly binds to the BBX14/15/16 loci and regulates their expression. Simultaneous knockdown of BBX14/15/16 resulted in significant downregulation of HY5 and upregulation of PIFs, suggesting that these factors participate in a feedback regulatory loop. Indeed, BBX14/15/16 induced HY5 promoter activity by binding to the HY5 promoter. The brassinosteroid-responsive gene TOUCH4 (TCH4) and several auxin-responsive SMALL AUXIN UPREGULATED RNA (SAUR) genes were upregulated in the BBX14/15/16 knockdown plants, suggesting that auxin and brassinosteroids might participate in BBX14/15/16-mediated hypocotyl regulation. Mutating the predicted BBX-binding sites in SAUR4 and TCH4 impaired their regulation by BBX14/15/16. We propose that BBX14/15/16, together with HY5 and PIFs, form a feedback loop that regulates the expression of auxin- and brassinosteroid-related genes to modulate hypocotyl elongation.